Tingkat Penggunaan dan Kepedulian PMRI Guru SD Kelas I, II, dan III Kota Banjarmasin - Muhammad Diva Almadani; Sutarto Hadi; Kamaliyah Kamaliyah (Jurnal Pendidikan Indonesia, 2025)
In developing PMRI, it is necessary to know the information of users, namely teachers, especially information related to the extent of teacher use and concern for the PMRI approach. This study aims to determine the level of use and concern for PMRI of elementary school teachers in grades I, II, and III in Banjarmasin City. The level of use and concern in this study is part of the Concern Based Adoption Model (CBAM). Quantitative descriptive research is a type of this research. The sampling technique for this study was purposive sampling. There were 4 schools that were included, where 33 teachers became respondents in the semi-open and closed questionnaires on the level of use and 39 teachers became respondents in the closed questionnaire on the level of concern. The results of the study showed, first, that the highest percentage was the level that described the situation in which teachers re-evaluated the quality of PMRI use, sought major modifications to current innovations to achieve greater impact on students, and examined new developments in the field. Second, teachers were identified as wanting to learn more about PMRI, but not making PMRI their sole concern, being interested in PMRI in terms of its impact only on themselves, in its implementation tending to be interested in collaboration, and teachers having some ideas about other approaches that might work better.